Theological Reflections on Bride Wealth In Africa: A Study of Selected Di.Nka Anglicans in Kakuma And Nairobi. Kenya - Wesonga, Martin Olando (Daystar University, School of Arts and Social Sciences, 2008)
Bride wealth has been a significant point of conflict between Christianity and African culture. Some African Christians have held this practice close to their heart. .Many times when bride wealth negotiations take place, questions arise as to whether this practice conflicts isith biblical teachings. Therefore studies on bride wealth are needed to help African Christians understand biblical teaching regarding the practice. The goal of this study therefore was to contribute theological reflections on bride v. ealth in the Dinka Anglican church, thereby prmiding lessons for elsewhere in Africa where bride wealth is practiced.. Three research questions were addressed: (l) how do the selected Dinka Anglicans understand bride wealth? (2) What makes them adhere to this practice? (3) What is the interface bem een the Dinka and biblical understandings of bride wealth? To achieve this end, qualitative research methods were employed including (l) participant observation. (2) semi-structured individual intervieil s. and (3) informal, unstructured interviews. The purposiie sample included ten priests, ten deacons and ten lay leaders. The data were analyzed qualitatively, identifying broad themes pertaining to the practice of bride wealth. The study showed that the selected Dinka Anglicans have held on to bride wealth practice to the extent that it affects the attendance of v, orship services on Sundays. Leaders who have not paid bride wealth are not to lead sersices on Sundass. The study highlighted Dinka perceptions of bride wealth. They generally beliese that bride is ealth gises the husband the right to control his i\ife in all affairs of the home. The wife becomes a servant once the bride ealth has been paid. Dinka Anglicans believe that paying bride wealth is a sign of manhood which should be followed whether one is a Christian or not. The study established that sometimes the bride's parents have abused this practice by charging high bride wealth, at times ranging from thirty to eighty cows. This is exorbitant for many young Dinka men. Tlfs study has set forth certain similarities and differences between biblical bride wealth practices, based on scriptures such as Gen. 34 and I Kings 18, and Dink-a bride wealth practices. Both involve the exchange of gifts to confirm the relationship bemeen a husband and ilife. plus their extended families. Another similarity is that there must be negotiations in the process of establishing bride "ealth, hence drassing together the two communities involved. Once bride wealth is paid, the woman is officially betrothed and consequently no man can approach her for marriage. Differences are found in that Dinka bride wealth is paid only in the form of cattle, 1Shereas examples of biblical bride wealth include a maid to accompany the bride, working to obtain the bride (e.g., Jacob), or the foreskins of Philistines (e.g., Dasid). Additionally, the Old Testament dictated that any man NAho had paid bride wealth was notthe case Finally, this study has resealed that bride wealth has merits and demerits. Bride ixealth is a symbol of friendship and social solidarity in bringing families together. Bride wealth. if abused, loses its meaning and purpose. Therefore, bride i'. ealth should be encouraged if it plays its original intention of solidifying relationships between the two parties and their communities, but it should be discouraged if it is abused.
Master of Theology in African Christianitv